THE INFLUENCE OF KAHOOT MEDIA USAGE ON STUDENTS' LEARNING INTEREST IN ISLAMIC RELIGIOUS EDUCATION (PAI) SUBJECT AT SMAN 1 BUNGURAN TIMUR - Muhammad Rasyid Ridho Rohman Rasyid; Septian Liandy; Novi Dwi Wahyuni (SOSIOEDUKASI, 2026)
This study aims to examine the influence of Kahoot-based instructional media on students' learning interest in Islamic Religious Education (PAI) at SMAN 1 Bunguran Timur, Natuna Regency, Riau Islands Province. A quantitative correlational approach was employed, involving 51 students as respondents. Data were collected through validated and reliable questionnaires and analyzed using Spearman Rank correlation via SPSS 26. The findings reveal that both Kahoot usage and students' learning interest fall within the moderate category, with mean scores of 58.51 and 56.25 respectively. The correlation analysis yielded a coefficient of rho = 0.508 with a significance value of 0.000, confirming a statistically significant influence of Kahoot-based media on PAI learning interest. The coefficient of determination further indicates that Kahoot contributes 26% to students' learning interest, while the remaining 74% is attributed to other variables. These findings suggest that although Kahoot demonstrably enhances learning interest, its full pedagogical potential remains unrealized due to limitations in digital infrastructure and implementation consistency inherent to this frontier archipelagic school context. Strengthening teacher competency and increasing the frequency of Kahoot utilization are recommended to elevate students' learning interest to a higher level.